A framework for evaluating management plans comprehensively - Verena M Trenkel; Marie‐Joëlle Rochet; Jake C Rice (Fish and Fisheries, 2015)
We present a framework for evaluating fisheries management plans comprehensively, both rebuilding plans and others. The framework includes a first rapid appraisal of the likelihood that the plan will result in management meeting its objectives, and guides subsequent quantitative analyses of potential weaknesses in the proposed plan. The framework includes four steps: (i) evaluating if a set of management objectives, if achieved, would result in a sustainable fishery, (ii) using qualitative analysis of a bio‐economic model to evaluate whether the set of stock management tactics might be capable of achieving the specified fisheries objectives, (iii) using empirical criteria derived from the literature to evaluate if other management measures in the plan related to the ecological, social or economic context of the fishery actually contribute to sustainability, and (iv) carrying out quantitative simulations to compare alternative implementation options. Generally, several management measures have to be combined to increase stock size without sacrificing the economic benefits to the fishers remaining in the fishery. We demonstrate application of the framework for evaluating the stock rebuilding plan for plaice ( Pleuronectes platessa ) and sole ( Solea solea ) in the North Sea and, the management measures currently in place for the roundnose grenadier ( Coryphaenoides rupestris ) stock exploited to the west of the British Isles.